Analisis Kualitas Genteng Beton Eco-Friendly dengan Cocofiber dan Cangkang Telur Ayam Sebagai Substitusi Pasir dan Semen - Ayu Rindiani; Restu Pradipta Eskananda; Hartono Hartono; Riza Susanti (Universitas Diponegoro, 2025)
One of the building construction materials needed is concrete tile for the roof of the building. However, concrete tiles have disadvantages, namely a higher price and heavyweight compared to other types of tiles. Therefore, innovations are needed to overcome these problems. This research utilizes coconut coir fiber waste with the same content as sand, which contains 30% silica fiber and is pozzolanic. Then, eggshell waste will be used as a substitute for cement because it contains the same compounds as cement, namely magnesium, iron, and calcium carbonate. The variations in the composition of coconut fibers and eggshells in the manufacture of concrete roof tiles as a partial substitute for the use of sand and cement are GA (0%: 0%), GB (34%: 6%), GC (40%: 6%), GD (32%: 8%), and GE (38%: 8%). In this study, the flexural strength test, water absorption test, water seepage resistance, as well as analyzing the weight and cost of concrete roof tiles were tested. The results of the most optimum concrete tile test are in the GD sample variation: a flexural load value of 1858.2 N, a porosity value of 8.53%, and a seepage test with no water droplets. Then, for the weight analysis of the GD variation, the concrete tile weighs 4.39 kg, and the production cost is IDR 3,017.00. The price differs from conventional roof tiles, Rp 611.00 or 16.84%. The test results show that it fulfilled SNI 0096: 2007.